Improving the performance of all-inorganic perovskite light-emitting diodes through using polymeric interlayers with a pendant design. (26th August 2021) - Chen, Chiung-Han; Lin, Yan-Cheng; Yang, Yun-Fang; Chiang, Yun-Chi; Li, Zhenchao; Yip, Hin-Lap; Chen, Wen-Chang; Chueh, Chu-Chen
Abstract : Despite demonstrating better photoluminescence quantum yield and ambient/operational stability than organic–inorganic hybrid perovskites, all-inorganic perovskites encounter the problem of inferior film quality and interfacial electrical properties. Abstract : Despite demonstrating higher photoluminescence quantum yield and better ambient and operational stability than organic–inorganic hybrid perovskites, all-inorganic perovskites encounter the problem of inferior film quality and interfacial electrical properties, which limits the resultant device performance. In this study, three polymers, P4a–c, bearing distinct pendant groups based on a similar conjugated group are synthesized and employed as an interlayer to modify the PEDOT:PSS/CsPbBr3 interface. Due to the pendant design, P4a–c possess deep-lying HOMO levels and high transparency across the visible range. The different structures of the pendant groups in P4a–c are shown to result in their different propensity in energy-level modulation and solid-state aggregation, which plays a non-trivial role in affecting the resulting device performance. Due to the more appropriate energy levels and better regulation of CsPbBr3 crystals, P4c with a polar bridge moiety is shown to better mediate the performance of the derived device. The P4c -mediated PeLED delivers six times enhanced luminance ( L max, ∼36 000 cd m −2 ) and 3.6 times enhanced external quantum efficiency (EQE, 2.16%) as compared to the control device (∼6000 cd m −2, 0.60%). Notably, all the devices using P4a–c interlayers deliver a lower turn-on voltage than the control device, clearly revealing the positive role of P4a–c interlayers on diminishing the barrier across the associated interface to improve charge injection efficiency.